2014
DOI: 10.1111/bju.12858
|View full text |Cite
|
Sign up to set email alerts
|

Medium‐term oncological outcomes for extended vs saturation biopsy and transrectal vs transperineal biopsy in active surveillance for prostate cancer

Abstract: ObjectiveTo assess, in men undergoing active surveillance (AS) for low-risk prostate cancer, whether saturation or transperineal biopsy altered oncological outcomes, compared with standard transrectal biopsy. Patients and MethodsRetrospective analysis of prospectively collected data from two cohorts with localised prostate cancer (1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012) undergoing AS. Prostate cancer-specific, metastasis-free and treatment-free survival, unfavo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 34 publications
0
45
1
2
Order By: Relevance
“…Linder et al [19] found that 214 AS candidates undergoing extended biopsy (124 cases) versus saturation biopsy (94 cases) showed no difference in the rate of upgrading and upstaging at definitive specimen based on biopsy technique (p = 0.26); on the contrary, Abouassaly et al [20] reported a more accurate assessment of the extent and grade of disease in men enrolled in AS protocol using saturation biopsy in when compared to extended biopsy. In addition, the saturation biopsy scheme increases progression to treatment in AS on comparison with extended prostate biopsy (10 cores) [21], thus improving the detection rate of PCa located solely in the anterior zone of the gland (about 10 % of the cases) [22]; on the other hand, no significant difference was detected in upgrading or morbidity between a 24-core template or a template gland based on volume gland with an average of 1 core per cc. [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Linder et al [19] found that 214 AS candidates undergoing extended biopsy (124 cases) versus saturation biopsy (94 cases) showed no difference in the rate of upgrading and upstaging at definitive specimen based on biopsy technique (p = 0.26); on the contrary, Abouassaly et al [20] reported a more accurate assessment of the extent and grade of disease in men enrolled in AS protocol using saturation biopsy in when compared to extended biopsy. In addition, the saturation biopsy scheme increases progression to treatment in AS on comparison with extended prostate biopsy (10 cores) [21], thus improving the detection rate of PCa located solely in the anterior zone of the gland (about 10 % of the cases) [22]; on the other hand, no significant difference was detected in upgrading or morbidity between a 24-core template or a template gland based on volume gland with an average of 1 core per cc. [23].…”
Section: Discussionmentioning
confidence: 99%
“…[23]. In recent years, mpMRI and mpMRI/TRUS fusion targeted biopsy have a good degree of accuracy in diagnosing clinically significant PCa secondary to the high sensitivity for lesion upgrading [8][9][10][11], especially when the cancer is located in the anterior prostate [6,7] or in the presence of micro-focal PCa (1 positive core of GS and GPC ≤ 5 %) [21]. Ouzzane et al [24] reporting on 281 patients in AS found that mpMRI targeted biopsy reclassified 10 % of patients who were eligible for AS based on systematic biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Thompson et al[25] recently compared different biopsy techniques (standard [<12 core, median 10] vs. saturation [>12 core, median 16], and transrectal vs transperineal biopsy), which showed that the AS protocol with saturation biopsies at the initial diagnosis and during follow-up reduced treatment-free survival during AS, while the AS protocol with transperineal biopsies reduced the likelihood of unfavorable disease in patients who underwent RP during follow-up. Similarly, Da Rosa et al [26] compared prospectively MRI-US fused targeted biopsy versus systematic ultrasound-guided biopsy for detecting clinically significant (CS) prostate cancer in patients on active surveillance and reported that MRI-ultrasound fusion biopsy detected CS cancer with far fewer cores and multiparametric MRI had a perfect negative predictive value in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Tablo 2'de farklı merkezlerin uygulamış olduğu takip protokolleri özetlenmiştir (10,11,12,13,14,15,16,17,18). Genel olarak Aİ'den definitif tedaviye geçmedeki nedenler progresyon olmadığı halde hastanın tercihi veya hastada oluşturduğu anksiyete, başlangıçtaki yüksek veya izlemde yükselen PSA değerleri, başlangıçtaki veya tekrar biyopsilerde saptanan yüksek evre, Gleason skor veya korlardaki yüksek kanser oranıdır (23).…”
Section: Aktif İzlem Protokolleri Ve Progresyonu Belirten Kriterlerunclassified
“…Zamanlamada standart olmamakla birlikte konfirmasyon biyopsisi sonrası genellikle 6-12 ay içinde, sonra da merkeze göre değişmekle birlikte yıllık veya 3-4 yıllık periyotlarla yapılmaktadır (10,11,12). Konfirmasyon biyopsisi sonrası hasta seçimine ve biyopsi tekniğine bağlı değişmekle birlikte %2,5-28 oranında Gleason derecesinde değişiklik bildirilmiştir (15). Takip biyopsilerinde ise farklı merkezlerde %22-30 oranında progresyon saptanmıştır (11,12,13).…”
Section: Biyopsiunclassified